Combined COI barcode‐based methods to avoid mislabelling of threatened species of deep‐sea skates. (24th June 2021) - Carugati, L.; Melis, R.; Cariani, A.; Cau, A.; Crobe, V.; Ferrari, A.; Follesa, M. C.; Geraci, M. L.; Iglésias, S. P.; Pesci, P.; Tinti, F.; Cannas, R.
Abstract: Skates are characterised by conservative body morphology which hampers identification and leads to frequent taxonomic confusion and market mislabelling. Accurate specimen classification is crucial for reliable stock assessments and effective conservation plans, otherwise the risk of extinction could be unnoticed. The misclassification issue is evident for the genus Dipturus, distributed worldwide, from the continental shelf and slope to the deep sea. In this study, barcode cytochrome oxidase I gene (COI) sequences were used along with species delimitation and specimen assignment methods to improve taxonomy and zoogeography of species of conservation interest inhabiting the Atlantic Ocean and Mediterranean Sea. In this study, we provided new evidence of the occurence of D. nidarosiensis in the Central‐Western Mediterranean Sea and the lack of Atlantic‐Mediterranean genetic divergence. The Atlantic endangered species D. laevis and D . batis clustered together under the same molecular operational taxonomic unit (MOTU) with any delimitation methods used, while the assignment approach correctly discriminated specimens into the two species. These results provided evidence that the presence of the barcode gap is not an essential predictor of identification success, but the use of different approaches is crucially needed for specimen classification, especially when threshold‐ or tree‐based methods result less powerful. The analyses also showed how different putative, vulnerable, species dwelling across South‐Western Atlantic and South‐Eastern Pacific are frequently misidentified in public sequence repositories. Our study emphasised the limits associated to public databases, highlighting the urgency to verify and implement the information deposited therein in order to guarantee accurate species identification and thus effective conservation measures for deep‐sea skates. Abstract : Accurate specimen classification is crucial for reliable stock assessments and effective conservation plans, otherwise the risk of extinction could be unnoticed. The misclassification issue is evident for a range of taxa, especially those with conserved body morphology, such as skates belonging to the genus Dipturus. The joint use of COI barcode‐based methods as species delimitation and specimen assignment approaches could improve the accuracy of specimen identification and help to build curate reference libraries. This study also emphasizes the limits associated to public databases, highlighting the urgency to verify, update and implement the information deposited therein in order to guarantee correct identification and thus effective species conservation measures.